2019
DOI: 10.1177/2050312119873513
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of substance abuse in Thai elderly: Ramathibodi Poison Center

Abstract: Objective: To describe substances, clinical manifestations, treatment, and medical outcomes of substance abuse exposures among older adults in Thailand. Method: This is a retrospective study of individuals aged 60 years or older with intentional abuse exposures reported to the Ramathibodi Poison Center from 1 January 2010 to 31 December 2017. Results: Forty-four cases were reported. The most common manifestation was somnolence (20, 45.5%). The most common substance used was kratom. There were 12 severe and fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Tobacco (nicotine) was the most commonly used substance (62.96%), followed by cannabis (11.11%), opioids (11.11%), sedative and hypnotics (8.88%), and Volatile substance (5.92%), which is similar to a study conducted in Thailand (15). A total of 1129 medicines were prescribed to 135 patients.…”
Section: Discussionsupporting
confidence: 69%
“…Tobacco (nicotine) was the most commonly used substance (62.96%), followed by cannabis (11.11%), opioids (11.11%), sedative and hypnotics (8.88%), and Volatile substance (5.92%), which is similar to a study conducted in Thailand (15). A total of 1129 medicines were prescribed to 135 patients.…”
Section: Discussionsupporting
confidence: 69%
“…A previous study in a hospital setting in Thailand examining 44 cases 7 indicated the factors that influence the increased substance abuse epidemiology, such as cultural aspects, political leanings, substance accessibility, and drug dependence acceptability. In terms of alcohol use, the current findings are consistent with various other studies.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in a hospital setting in Thailand examining 44 cases 7 Figure 4 The odds ratios for males (female as baseline, P < 0.001) less than 1 for the occurrence of nervous system diseases over the 5-year period from 2014 to 2018.…”
Section: Mental Behavioural and Neurodevelopmental Disordersmentioning
confidence: 95%
See 1 more Smart Citation
“…Drug abuse problems in Thai men stem from various reasons, resulting in domestic violence, learning-related issues, unhealthy relationships, toxic relationships, and co-dependent relationships (Ruangritchankul & Srisuma, 2019 ; Thumwong & Kanato, 2020 ). These reasons may be rooted in environmental factors or the emulation of certain behaviors observed in society or on social media, while individual curiosity may also play a role.…”
Section: Introductionmentioning
confidence: 99%